Formulation and evaluation of gastroretentive drug delivery system of eprosartanmesylate - Vantimita, Sarovar Reddy; Jeganath, S. (International journal of health sciences, 2022)
It had became a challenging experience and effort for a formulator to develop and innovate a drug with maximum bioavailability. Objective: In the present study the focus of research is in the treatment of Hypertension, which is one of the most prevalent cardiovascular diseases in the world, affecting a big proportion of the adult and old age population. Eprosartan mesylate(EPM) is angiotensin-II receptor antagonist used for the treatment of high blood pressure. The drug has poor bioavailability due to limited oral absorption and maximum absorption at proximal intestine. This warrants and offers the use of Gastro Retentive Drug Delivery System (GRDDS) for sustained release formulation in order to achieve prolonged action and to improve patients compliance. Method: Wet granulation technique was selected for preparation of tablets and the drug is formulated with hydroxyl propyl methyl cellulose K100m, hydroxyl propyl methyl cellulose K15m, polyox WSR coagulant, polyox WSR301,polyox WSR N80, Lactose Monohydrate, Micro crystalline cellulose(Avicel), magnesium sterate, ethylcellulose, sodium bicarbonate, tromethamine, etc. Results: For around twenty formulations were made and evaluated for General appearance, Thickness, Hardness or Crushing strength Test, Friability Test, Estimation of drug content.